2014
DOI: 10.1186/2050-3385-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Eyes in the sky: linking satellite oceanography and biotelemetry to explore habitat selection by basking sharks

Abstract: Background: Satellite-based oceanographic data products are a valuable source of information on potential resource availability for marine species. Satellite oceanography data may be particularly useful in biotelemetry studies on marine species that feed at low trophic levels, such as zooplanktivorous whales, sharks, and rays. The basking shark, Cetorhinus maximus, is a well-documented zooplanktivore in the western North Atlantic, yet little is known of its movements and spatial ecology in this region. A combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…Baduini (1995) and Darling and Keogh (1994) reported that individual basking sharks spent up to 30 or 42 days in Monterey Bay, CA, or Clayoquot Sound, Vancouver Island, Canada, respectively. Similar short-term residence times have been reported for basking sharks in coastal regions in the Atlantic Ocean (Sims et al, 2003;Gore et al, 2008;Sims, 2008;Skomal et al, 2009;Curtis et al, 2014;Doherty et al, 2017;Braun et al, 2018).…”
Section: Geographic Movements and Essential Habitatsupporting
confidence: 81%
See 3 more Smart Citations
“…Baduini (1995) and Darling and Keogh (1994) reported that individual basking sharks spent up to 30 or 42 days in Monterey Bay, CA, or Clayoquot Sound, Vancouver Island, Canada, respectively. Similar short-term residence times have been reported for basking sharks in coastal regions in the Atlantic Ocean (Sims et al, 2003;Gore et al, 2008;Sims, 2008;Skomal et al, 2009;Curtis et al, 2014;Doherty et al, 2017;Braun et al, 2018).…”
Section: Geographic Movements and Essential Habitatsupporting
confidence: 81%
“…C. pacificus developmental stages (C) IV and V contain a large lipid droplet and are energetically dense. The CIV and CV stage of C. finmarchicus are targeted by basking sharks in the western North Atlantic (Baduini, 1995;Siders et al, 2013;Curtis et al, 2014). Off CA the CIV and CV stages occur year around but are most abundant in surface waters from April through October (Johnson and Checkley, 2004), although high concentrations of CV can also be found at depth during periods of diapause (see below).…”
Section: Geographic Movements and Essential Habitatmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not generally possible for pelagic macropredatory sharks because environmental fields of their schooling fish prey for example are very difficult to obtain over sufficiently large scales to support analysis in relation to pelagic shark movements and behavior (for exceptions see Makris et al, 2006Makris et al, , 2009. Previous biotelemetry studies in the North Atlantic have revealed that basking sharks undertake extensive horizontal and vertical movements associated with oceanic and inner-shelf frontal zones, areas typically characterized by high primary production and zooplankton densities (Sims et al, 2003;Skomal et al, 2009;Curtis et al, 2014;Doherty et al, 2017), and also highlighted behavioral shifts in vertical movements linked to changes in the behavior of zooplankton (Sims et al, 2005). In contrast to filter feeding, the blue shark (Prionace glauca) is an oceanic, ram-feeding macropredator occurring in all tropical and temperate seas; in the Atlantic Ocean, blue sharks range from Newfoundland to Argentina in the west, over the entire mid-Atlantic, and from Norway to South Africa in the east (Compagno, 1984;Motta and Huber, 2012).…”
Section: Introductionmentioning
confidence: 99%